Periodna preglednica in zgradba atomov - Strnad, Janez (Obzornik za matematiko in fiziko, 2011)
The International year od chemistry 2011 "will celebrate the achievements of chemistry and its contributions to the well-being of mankind". On this occasion it appears worthwhile to review the quantum roots of the periodic table of elements. This is a point of contact of physics and chemistry, important to teaching of both. In chemistry the discussion is oftem begun with the statistical model of atom. In this model the order on which electons are filling the subshells ?$(n,l)?, characterized by the principal quantum number ?$n$? and the orbital quantum number ?$l$?, can be understood. The order is expressed by the Madelung rule: the subshells fill up in the order of the increasing sum ?$n+l$? and for equal sums in the order of increasing ?$n$?.
Keywords: fizika; kemija; Madelungovo pravilo; obhodna vrtilna količina; Thomas-Fermijev model; zgradba atomov